Reception of Students of SMA Negeri 5 Sarolangun for The Silent Piece (1949) Music Composition by John Cage - Muhammad Egi; Nusyirwan Nusyirwan; Selvi Kasman; Rosmegawaty Tindaon (Gondang: Jurnal Seni dan Budaya, 2023)
Broadly speaking, we can associate music with sound. The association received a "challenge" from John Cage, an American composer of the Avand-Garde era who in 1949 made the most famous work, namely 4'33' or can be called four thirty three, the purpose of this research/article is to discuss responses, responses, interpretation, and the percentage of student respondents to John Cage's unconventional music. The author uses a qualitative and quantitative mix-method research method in data collection and data analysis. Discussion and analysis of data using the theory of reception and interpretation. Various receptions/responses were presented by the students, some of whom responded "silence, murmuring, and wondering". The interpretation presented by the students is th at the answers given are subjective and not influenced by anyone. The quantitative data that the researcher has analyzed provides an overview of the percentage of students listening to John Cage 4'33' in the form of a percentage graph.